Penerapan Algoritme Jaringan Syaraf Tiruan Backpropagation pada Pengklasifikasian Status Gizi Balita - Maria Sartika Tambun; Muhammad Tanzil Furqon; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Growth and development of children is an important thing that can be known by the assessment of nutritional status. A benchmark of a fulfilled accomplishment of nutrients in children who can be classified with severe obesity. Assessment of the nutritional status of toddlers can be determined by measuring the body known as